2018
DOI: 10.1111/dom.13317
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal glucagon for hypoglycaemia in diabetic patients. An old dream is becoming reality?

Abstract: In 1983 it was shown that glucagon administered intranasally (IN) was absorbed through the nasal mucosa and increased blood glucose in healthy subjects. Shortly thereafter, it was shown that IN glucagon counteracts with hypoglycaemia in insulin-treated diabetic patients. In spite of this evidence, IN glucagon was not developed by any pharmaceutical company before 2010, when renewed interest led to intensive evaluation of a possible remedy for hypoglycaemia in insulin-treated diabetic adults and children. IN gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…2,11 In 2018, outside a clinical setting, injection of 1 mg of glucagon via a needle and syringe by another person was the only available treatment for severe hypoglycemia. 12,13 The limitation with this method is that glucagon is unstable in solution; thus, the current glucagon emergency kits are complex, requiring the user to reconstitute a lyophilized powder in a diluent and then deliver it via intramuscular or subcutaneous injection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,11 In 2018, outside a clinical setting, injection of 1 mg of glucagon via a needle and syringe by another person was the only available treatment for severe hypoglycemia. 12,13 The limitation with this method is that glucagon is unstable in solution; thus, the current glucagon emergency kits are complex, requiring the user to reconstitute a lyophilized powder in a diluent and then deliver it via intramuscular or subcutaneous injection.…”
mentioning
confidence: 99%
“…Errors in handling, including difficulty in opening the pack, sheath removal, mixing, and damaging the needle, and in administering the full dose of glucagon have been experienced. 12,14,15 Moreover, caregivers or acquaintances may not have received education on how to use the glucagon kit or may have a fear of needles and, as a result, may be too frightened to administer glucagon. 16e19 In a simulated glucagon administration study that included 136 parents of teenagers or young children with diabetes, 69% had handling difficulties that ranged from opening the container and mixing to drawing the correct dose into the syringe.…”
mentioning
confidence: 99%
“…It also allows prolonged mucosal contact time which enhances drug absorption [ 75 ]. There are a few intranasal powder formulations available in the market, including sumatriptan for the treatment of migraine [ 76 , 77 ] and glucagon for use in hypoglycemic emergency [ 78 ]. Both these demonstrate good safety profile, fast absorption and rapid onset of action.…”
Section: Intranasal Deliverymentioning
confidence: 99%
“…A novel, needle-free, easy-to-use form of glucagon is desirable to overcome the mentioned limitations of parenteral glucagon for the treatment of severe hypoglycaemia 23…”
Section: Nasal Glucagon For Severe Hypoglycaemiamentioning
confidence: 99%
“…Nasal glucagon was first shown to be passively absorbed through the nasal mucosa and to increase blood glucose levels in healthy subjects in 1983 24. Although small studies using intranasal glucagon solutions and intranasal glucagon powders also showed positive results in adults and children with type 1 diabetes, at that moment the pharmaceutical industry did not take the opportunity to develop this formulation 23. Currently, a nasal formulation of glucagon is undergoing development.…”
Section: Nasal Glucagon For Severe Hypoglycaemiamentioning
confidence: 99%